THE EFFECTIVENESS OF THE ROLE OF THE SUPERVISORY BOARD OF THE CORRUPTION ERADICATION COMMISSION IN IMPLEMENTING WIRING - Bonifansius Sulimas; Eriyantouw Wahid; Rosdiana Saleh (CV. RADJA PUBLIKA, 2024)
The revision of Law No. 19 of 2019 on the Second Amendment to Law No. 30 of 2002 on the Corruption Eradication Commission (KPK) has raised a number of pros and cons regarding the additional articles. The existence of the Supervisory Board is considered to weaken the independence of the KPK and is at risk of expanding the authority of the addition of Article 12B, paragraph (1), which states